Correlation of hepatic transient elastography measurements and abdominal adiposity in children: A cross-sectional study - Yii-Shiuan Lee; Shih-Hsi Song; Tzee-Chung Wu; Shang-Liang Wu; Ching-Feng Huang (Elsevier, 2023)
Background: Transient elastography is a non-invasive assessment of steatosis (measured as the controlled attenuation parameter, [CAP]) and fibrosis (measured as liver stiffness measurement, [LSM]) in patients with pediatric non-alcoholic fatty liver disease (NAFLD). Abdominal adiposity is considered the most important factor for metabolic dysregulation including NAFLD. However, there is lack of a correlation between transient elastography measurements and abdominal adiposity. Accordingly, this study aimed to assess the correlation between transient elastography measurements and abdominal adiposity in children. Methods: This cross-sectional study included 137 children who visited the Taipei Veterans General Hospital. Hepatic steatosis (CAP) and fibrosis (LSM), were assessed by transient elastography. Abdominal adiposity including subcutaneous adipose tissue (SAT), visceral adipose tissue (VAT), and preperitoneal adipose tissue (PPT) was assessed using abdominal sonography. The correlation between transient elastography measurements and abdominal adiposity was assessed using multiple linear regression. Results: In total, 137 children were included in this study. SAT and VAT were significantly associated with CAP, whereas SAT was significantly associated with LSM. An increment of 1 mm in SAT increased CAP and LSM by 5.56 dB/m and 0.06 kPa, respectively. Conclusion: Certain abdominal adiposities, especially SAT, are significantly associated with CAP and LSM, as determined by transient elastography. Simple abdominal adiposity measured using sonography may be useful for the early detection of pediatric NAFLD.